A microelectrode impedance method to measure interaction of cells - Gomes, Henrique L. (2015)
An impedance method was developed to determine how immune system cells (hemocyte) interact with intruder cells (parasites). When the hemocyte cells interact with the parasites, they cause a defensive reaction and the parasites start to aggregate in clusters. The level of aggregation is a measure of the host-parasite interaction, and provides information about the efficiency of the immune system response. The cell aggregation is monitored using a set of microelectrodes. The impedance spectrum is measured between each individual microelectrode and a large reference electrode. As the cells starts to aggregate and settle down towards the microelectrode array the impedance of the system is changed. It is shown that the system impedance is very sensitive to the level of cell aggregation and can be used to monitor in real time the interaction between hemocyte cells and parasites.